Perceptual Threshold Level for the Tactile Stimulation and Response Features of ERD/ERS-Based Specific Indices Upon Changes in High-Frequency Vibrations - Choi, Mi-Hyun; Kim, Boseong; Kim, Hyung-Sik; Gim, Seon-Young; Kim, Woo-Ram; Chung, Soon-Cheol (Frontiers in Human Neuroscience, 2017)
This study was conducted to identify characteristics of the perceptual threshold level and EEG responses to vibrotactile stimulations at various high frequencies, and to examine the possibility of distinguishing vibrotactile stimulations by frequency through such response characteristics. The vibrotactile stimulations of six frequencies (150, 200, 225, 250, 275, and 300 Hz) were exerted on the first joint of right index finger. The perceptual threshold level was defined as the first minimum perceived intensity when the intensity stimulation was exerted step by step at each vibration frequency. EEG response characteristics were investigated by examining a single index corresponding to the peak or area of event-related desynchronization/synchronization (ERD/ERS) and seven specific indices derived by combining the single ERD/ERS indices. There was a significant difference in the perceptual threshold level across different frequencies. Specifically, the differences in vibration stimulus between 150 Hz and 200 Hz, and between 150 Hz and 225 Hz were significant. Of the EEG response characteristics, the single index of the peak or area of ERD/ERS did not show a significant difference by frequency. However, (ERS-ERD), ERD×(ERS-ERD), and ERS×(ERS-ERD) showed a significant difference between vibration stimulations at 150 Hz and 200 Hz, and between vibration stimulations at 150 Hz and 225 Hz, among the specific indices combined using the peak values of ERD/ERS. Furthermore, ERS×(ERS-ERD) showed a significant difference between 150 Hz and 225 Hz, and between 225 Hz and 275 Hz among the specific indices combined using the area of ERD/ERS. The perceptual threshold level and the specific indices of ERD/ERS suggested in the present study can be used as quantitative measurement indices to distinguish high-frequency vibration stimulation.